The cloning and characterization of an α-amylase and a branching enzyme from Butyrivibrio fibrisolvens H17c and their expression in Escherichia coli - Rumbak, Elaine (Department of Molecular and Cell Biology, 2016)
Bibliography: pages 145-172.